The Nexus Between ESG Risk, Capital Structure, Profitability, and Firm Value: Firm Size as a Moderator - Ashari, Vegy Tasya; Rahmawati, Mia Ika (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to analyze the influence of ESG Risk Rating, capital structure, and profitability on firm value, and examine the role of firm size as a moderating variable. The study sample was companies listed in the IDX ESG Leaders (ESGL) index on the Indonesia Stock Exchange during the 2021–2023 period, with a total of 90 observations. Data analysis was performed using Moderated Regression Analysis (MRA) with the help of SPSS version 25. The results show that ESG Risk Rating has a significant negative effect on firm value, while capital structure has a significant positive effect and profitability has a significant negative effect. Firm size is proven to weaken the effect of capital structure and strengthen the effect of profitability on firm value, but does not moderate the relationship between ESG Risk Rating and firm value. These findings emphasize the important role of financial factors and profitability in shaping firm value by considering the influence of firm size.